Six Basic Energy Management At Middle-Aged Adults Moslem - Raras Sutatminingsih (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
This research aims to examine how Six Basic Energy Management (physical, instinctive, intellectual, emotional, spiritual and transcendental energy) in middle-aged individuals in Medan, then it is studied based on existing theories and research results. This research was conducted using quantitative descriptive methods. The population in this research were middle-aged adults, aged between 40-59 years old, Muslim and living in the Medan. Sampling is done by using purposive sampling technique. This research uses a Six Basic Energy management scale which is modified based on the Six Basic Energy Management concept from Suryanto (2008). The results showed that the respondents generally had six basic energy management which was in the quite constructive category, where the analysis of the management of each dimension of six basic energy (physical energy, instinctive, intellectual, emotional, spiritual and transcendental) in the research respondents was in a fairly constructive category. It means that the respondents are able to manage the Six Basic Energy they have so they can be profitable in their lives. It means that the respondents are able to manage their Six Basic Energy so they can be profitable in their lives.